Reading-Related Activities in English Textbook for Grade 7th Junior High School and How Teacher Exploited Texts in the Classroom - Ni Made Yuni Karya Dewi; Luh Putu Artini; Luh Gede Eka Wahyuni (Universitas Pendidikan Ganesha, 2022)
The use of textbook in the reading class is one of the efforts that can be done by teachers in helping students to improve their abilities, namely by applying reading-related activities contained in the textbooks to the learning process in the classroom. This study aims at analyzing reading-related activities that are available in English textbook entitled “Effective English; Bahasa Inggris untuk SMP/MTs Kelas VII” was used for 7th Grade students and describing how the reading texts were exploited by the English teacher in the classroom. This study employed a qualitative descriptive research design. The subjects of this study were seventh grade students and an English teacher at Junior High School. Data were collected through document analysis, class observations, and interviews. The data in this study were analyzed through the data analysis procedures which include data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are only a few reading-related activities in the English textbook entitled, namely lexical items and questioning activity. Meanwhile, the teacher’s strategies in exploiting the reading texts were also limited as the teacher closely used reading-related activities available in the textbook. This study was limited in time, number of subjects, and data sources so that further research is suggested for more generalizable findings.